SEMIOTIC ANALYSIS OF THE MEANING OF WOOD CARVINGS IN TONGKONAN - Soekarno Buhari Pasyah (Universitas Negeri Makassar, 2022)
The symbol on the wooden carving of the Toraja traditional house (Tongkonan) is an important part of its construction, so the purpose of this article is to describe and analyze the symbol of power. This exploration uses subjective interpretive examination techniques, breaks down and describes the significance of things that are concentrated considering the reality on the ground, involves key witnesses as sources of information, utilizes essential and optional information through top-down meetings, field perceptions, action documentation, and references related to this examination. The semiotic model developed by Charles Sanders Peirce is used in this research data analysis method. The Toraja traditional house has sixty-seven types of wood carvings, but only four represent the symbol of the strength of the Tongkonan owner for the present and the future. In addition, the Tongkonan carving patterns represent the social status of the Toraja people. From the underlying information From information obtained, it can be said that the carvings on the Tongkonan depict images of objects and animals that exist in the Toraja people. The message contained in cutting the Tongkonan is a way of thinking about the life of the Toraja people themselves.